Investing Back Home : The Potential Economic Role of the Caribbean Diaspora - World Bank Group (World Bank, Washington, DC, 2016)
This study was initiated as a result of interest expressed by Caribbean Governors attending the 2014 World Bank–International Monetary Fund Annual Meetings to tap into the regional Diaspora investor community to fund investment needs across the region. The overall development objective of the study is to formulate options that can help mobilize Diaspora capital in the form of private investment in productive investable assets, including start-ups and other business enterprises, social infrastructure (e.g., schools, hospitals), physical infrastructure (e.g., energy, transport, water), and public market (i.e., liquid) investments. Diaspora-sourced investment flow into these types of productive assets can ultimately serve to spur economic growth and job creation, which is a clear imperative in this region. The survey also builds on the promising conclusions of the 2013 Information for Development Program (infoDev) survey, which identified the potential demand for such investments within the global Caribbean Diaspora. This document encompasses a broad survey of 14 countries in the Caribbean as well as an in-depth analysis of four countries in particular Barbados, Jamaica, St. Lucia, and Trinidad and Tobago. The framework for this prefeasibility assessment comprised four areas of analysis, focused on (1) sizing the Diaspora population and its investment potential and interest; (2) conducting market research on the investment landscape, including investable assets and market drivers and impediments; (3) analyzing the legal and regulatory framework for investments in the Caribbean; and (4) identifying distribution channels and convening platforms that can offer, host, or advocate for a potential Caribbean regional Diaspora initiative. To conclude, to pursue targeted Diaspora-focused initiatives, more resources need to be committed to conducting robust Diaspora sizing and mapping exercises in select countries so as to segregate the Diaspora by generation, income, and net worth to better understand affinity and investment capacity as any menu of initiatives designed to mobilize Diaspora investment will need to be segregated to target specific groups of the Diaspora by investment capacity and preference.